Assessment of regional variation in the management of heart failure with a preserved ejection fraction between the Russian Federation and the European Union: the results of the international survey - Nathan Mewton; Clara Saldarriaga; Irina Dyachuk; Han Naung Tun; Ilya Giverts; Anastasia Shchendrygina; Natalia Cherkasova; Aleksandr Suvorov; Irina Komarova; Nadezhda Mukhina; Violetta Sitnikova; Elena Kuzheleva; et al. (BMJ Open)
Objectives Regional differences in heart failure with preserved ejection fraction (HFpEF) care have been reported. We aimed to assess a physician-reported HFpEF management in the Russian Federation (RF) and a variation in the diagnosis and treatment of HFpEF between the RF and the European Union (EU).Design/settings It is a post hoc analysis of an academic web-based international HFpEF designed as a cross-sectional survey and conducted between May 2023 and July 2023.Participants Medical doctors who work in the fields of cardiology and general medicine.Results Among 1460 medical doctors who completed the study were 166 Russian and 646 European specialists. The responders were comparable across the groups in most of the baseline characteristics, except that RF specialists were less likely to be heart failure specialists (RF: 2% vs EU: 26%) and less often worked in academic environments (RF: 17% vs EU: 61%). The utilisation of specific echocardiography parameters (RF: 66% vs EU: 80%) and natriuretic peptides (RF: 83% vs EU: 91%) to establish a diagnosis of HFpEF was less frequent in RF compared with EU, while HFpEF scores were more likely to be used by Russian physicians (RF: 58% vs EU: 40%). In the settings when all HF medications are available, responders of both regions prioritised sodium-glucose co-transporter type 2 inhibitors (SGLT2is) (mean rank: RF: 2.6 (IQR: 2.3–3) vs EU: 2.3 (IQR: 2.2–2.5)), followed by diuretics in the EU and ACE inhibitors in the RF. Every second responder in both regions preferred SGLT-2is if only one drug was available (RF: 57% vs EU 51%).Conclusions The results reveal discrepancies in physician-reported HFpEF management between RF and EU responders, particularly in the diagnostic workup. Although the utilisation of relevant diagnostic tests was lower in the RF compared with the EU, these were used by two-thirds of Russian respondents. Nevertheless, further measures are required to improve the care of HFpEF patients in the RF.